Study of Psychiatric Morbidity of Patients Attending Free Mental Health Check Up Camp, Simara, Bara District of Nepal - Sedain, CP (Journal of Chitwan Medical College, 2013)
Maryknoll Nepal has been running community mental health clinics in different parts of the country. The aim of the study was to find out psychiatric morbidity of patients attending Maryknoll free check up clinic Simara, Bara district of Nepal. A prospective cross-sectional study comprising of all consecutive patients attending Maryknoll free check up clinic Simara, Bara district, Nepal. All the patients attending the free clinics were taken as case. The study was performed in the month January 2009. Demographic data and disease profile of 87 patients attending the clinic were analyzed. The ratios and proportions were used for statistical analysis. Data in Simara free mental health clinic shows that the male to female ratio was 0.55:0.44. The age group 30-39(N-25, 28.74%) followed by age group 20-29 (N-19, 21.84%) was the most common. The farmer were (N-49, 56.31 %) the most common visitor. The highest number of cases were depressive disorder (N-16, 18.93 %) followed by mania/BPAD (N-14, 16.09 %) and Schizophrenia (N-12, 13.73 %). Most of patients attending Simara free mental health clinic were farmers of age group 20-40. The most common incidence of psychiatric illness attending the free clinic were depressive disorder and mania/BPAD. DOI: http://dx.doi.org/10.3126/jcmc.v3i2.8443 Journal of Chitwan Medical College Vol.3(2) 2013 45-48